Images of fear in language communities and cultures: the case of Slavic, Germanic, Romance, and Celtic languages: Образы страха в культурно-языковых сообществах (на материале славянских, германских и кельтских языков) - Dronov, Pavel; Ioanesyan, Yevgeniya; Kovshova, Maria (Przegląd Wschodnioeuropejski, 2020)
Being a case study of lexical and figurative units in Slavic, Germanic, and Romance languages, as well as Irish, the paper deals with the means of naming fear, revealing its connection to other concepts. The paper covers models of naming this emotion represented in the underlying metaphors, synchronous polysemy and phraseology. As the analysis shows, different languages have different primary associations with fear, e.g. darkness, uncertainty, insecurity, loneliness, high altitude, etc. To investigate underlying images and metaphors found in the naïve worldview, the authors use the corpus-based approach, as well as (for the Russian data) the technique of modified semantic differential. The technique, based on an experiment involving Russianspeaking respondents, allowed for distinguishing and detailing criteria of perceiving names and predicates denoting fear.